2017
DOI: 10.1038/ajg.2017.55
|View full text |Cite
|
Sign up to set email alerts
|

A Serological Biopsy Using Five Stomach-Specific Circulating Biomarkers for Gastric Cancer Risk Assessment: A Multi-Phase Study

Abstract: A serological biopsy composed of the five stomach-specific circulating biomarkers could be used to identify high-risk individuals for further diagnostic gastroscopy, and to stratify individuals' risk of developing GC and thus to guide targeted screening and precision prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
3
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(132 citation statements)
references
References 41 publications
4
117
3
8
Order By: Relevance
“…Combined detection of serum pepsinogen I and II, H. pylori antibody, and gastrin‐17 (known as a “serology biopsy”) has proved useful in screening for gastric mucosal atrophy, a high‐risk group of gastric cancer. Non‐invasive serological screening combined with endoscopy can help improve the effect of gastric cancer screening . A total of 14 929 serum samples and endoscopic data from China showed that age, sex, pepsin ratio < 3.89, gastrin‐17 > 1.50 pmol/L, H. pylori antibody positive, salted food, and fried food are the seven high‐risk factors for gastric cancer .…”
Section: Helicobacter Pylori Screening and Eradication Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Combined detection of serum pepsinogen I and II, H. pylori antibody, and gastrin‐17 (known as a “serology biopsy”) has proved useful in screening for gastric mucosal atrophy, a high‐risk group of gastric cancer. Non‐invasive serological screening combined with endoscopy can help improve the effect of gastric cancer screening . A total of 14 929 serum samples and endoscopic data from China showed that age, sex, pepsin ratio < 3.89, gastrin‐17 > 1.50 pmol/L, H. pylori antibody positive, salted food, and fried food are the seven high‐risk factors for gastric cancer .…”
Section: Helicobacter Pylori Screening and Eradication Strategymentioning
confidence: 99%
“…Non-invasive serological screening combined with endoscopy can help improve the effect of gastric cancer screening. 41 A total of 14 929 serum samples and endoscopic data from China showed that age, sex, pepsin ratio < 3.89, gastrin-17 > 1.50 pmol/L, H. pylori antibody positive, salted food, and fried food are the seven high-risk factors for gastric cancer. 42 The gastric cancer risk score scale was developed based on these factors and has been used for the screening of populations at high risk for gastric cancer in China.…”
Section: Y Du Et Almentioning
confidence: 99%
“…[19][20][21][22] No investigation has referred to an association between either EBV serology and GC prognosis or EBV and serum gastric function indicators such as pepsinogen I (PGI), pepsinogen II (PGII), pepsinogen I/II (PGI/II), and gastrin-17 (G-17), which could reflect the functional status of gastric mucosa and were thus recognized as indicators for the early detection of GC. 23 In addition, it remains unclear whether the EBV serologic assay has the potential to be a biomarker for GC prediction and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this, the ABCD screening method was used in Japan as gastric cancer risk stratification for developing appropriate inspection strategies. [164][165][166][167][168] A recent study in China 169 showed that the combined detection of PG, gastrin-17, and anti-H. pylori antibody could stratify the risk of gastric cancer and identify highrisk patients for gastroscopy. The PG I/II ratio was negatively correlated with OLGA staging.…”
Section: Statement 45mentioning
confidence: 99%